Wave in deck loads using Lagrangian Momentum Absorption (LMA) scheme - Koay, Wen Xin (Universiti Teknologi PETRONAS, 2021)
When the water surface elevation exceeds the deck elevation and inundates the deck of fixed offshore structures, the resulting loads which are known as wave-in-deck loading leads to a step change in the loads acting on the structure. Given its importance, for predicting WID, a number of approaches exist, such as the well-known drag formulation and Kaplan’s model. However, an important shortcoming of these models is the large number of empirical coefficients that ought to be obtained experimentally. A recently proposed model, known as Lagrangian Momentum Absorption (LMA) scheme overcomes these limitations by basing it upon the momentum dissipation that occurs during WID loading, removing the need for a large number of empirically tuned coefficients. This model can incorporate the details of the structure including its’ porosity.